Qualification and Testing of a Large Hot Slumped Secondary Mirror for Schwarzschild–Couder Imaging Air Cherenkov Telescopes. (25th March 2016) - Rodeghiero, G.; Giro, E.; Canestrari, R.; Pernechele, C.; Sironi, G.; Pareschi, G.; Lessio, L.; Conconi, P.
Abstract: Dual-mirror Schwarzschild–Couder (SC) telescopes are based on highly aspherical optics, and they represent a novel design in the world of very high energy astrophysics. This work addresses the realization and the qualification of the secondary mirror for an SC telescope, named ASTRI, developed in the context of the Cherenkov Telescope Array Observatory. The discussion surveys the overall development from the early design concept to the final acceptance optical tests.